Sunday
March 26, 2017

Post a New Question

Posted by on .

I'm trying to rearange this
0 = Xo + 2^-1 a t^2
for t
I've been told that it is

(a^-1 2x)^(2^-1)

but I do not see how please show me step by step how you get that

0 - Xo = Xo - Xo + 2^-1 a t^2
(-Xo = 2^-1 a t^2) a^-1 2
(a^-1 (2-Xo) = t^2)^(2^-1)
(a^-1 (2 - Xo))^(2^-1)

please show me how to do this as i'm getting negetive number imaginary
show me step by step how to rearang please not just the rearanged equation but how you rearange it because i do not get it

  • Physics - ,

    see mathmates response to the question before. I don't understand how you make it so complicated.

    x=x0+ vo*t +1/2 gt^2
    let x0, vo be zero (so x downward will be negative).

    x=1/2 g t^2

    t=sqrt (2x/g)-8.8 sec about

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question